Value engineering as the way of quality problems solving in the steel construction management - Stasiak-Betlejewska, Renata (Manufacturing Technology Journal, 2012)
The study aim was discussion on the steel construction production with regard to quality problems and its analysis by using value engineering. The most important elements of the work should, however, discuss how an important factor for the company's production and quality management are. Based on this explicit purpose developed the following hypothesis: identification of the nonconformities location in the production process of steel constructions and its causes contributes to the production improvement. The research result is identification of nonconformities formation areas and presentation of the production process improvement methodology by applying of quality tools and value engineering idea as well. The research object was chosen company producing steel constructions for buildings. The examination research findings come from 2011 year.
Keywords: quality; production management; steel construction; value engineering